Laboratory testing of cross-country skis – Investigating tribometer precision on laboratory-grown dendritic snow. (April 2022) - Auganæs, Sondre Bergtun; Buene, Audun Formo; Klein-Paste, Alex
Abstract: Small differences in ski-snow friction results in large time gaps, and glide testing is therefore an important part of racing. To test ski-snow friction without the influence of changing weather, snow conditions and skier position is therefore valuable. In this study, a full-scale ski-snow tribometer was developed and we investigated the degree of precision obtainable for different snow types, speeds, between separate ski tracks and snow surface preparations. The precision within new snow test tracks was 1.45%, and changing between parallel tracks added another 1.03% to the precision. Measurements across several dendritic snow testbeds were associated with a further 2.39% contribution to the precision. On aged snow, better precision was obtained within and between tracks on the same snow surface. Graphical Abstract: ga1 Highlights: For the first time a tribometer for full-scale cross-country ski has been tested on laboratory-grown dendritic snow. Tribometer precision contributions from the measurement unit, track position and snow testbed preparation were determined. Measurements on dendritic snow have sufficient precision to distinguish skis with Δμ < 0.001. Polishing of the ski tracks and its effect on μ has been investigated by non-destructive elastomeric 3D surface imaging. Reasonable reproducibility of snow testbeds was achieved.